2022
DOI: 10.1136/jim-2021-001908
|View full text |Cite
|
Sign up to set email alerts
|

Impact on the Fitness of N95 Masks with Extended Use/Limited Reuse and Dry Heat Decontamination

Abstract: Substandard use of N95 masks, sometimes combined with dry heat decontamination, lacks safety data. We evaluated the impact of these practices on the fitness of N95 masks. This is a non-human subject research conducted from July to October 2020. 155 masks were used by 12 healthcare workers during 10-hour shifts. Masks were collected at the end of the shift and if the number of donnings/doffings was less than five (‘modified extended use’, ME) or whenever this number reached five (‘limited reuse’, LR), per the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
(22 reference statements)
0
5
0
2
Order By: Relevance
“…Additional work studying the electrostatic charge on mask filter layers, which is partially responsible for filtering of small particles by electrostatic adsorption, found that dry heat treatment at low humidities (< 30% RH) and low temperatures (< 100 °C) for 20 cycles did not decay the electrostatic charges and the efficiency of the filters ( Campos et al, 2020 , Liao et al, 2020 ). Fit tests conducted by Zha et al after one cycle of dry heat decontamination at 75 °C for 30 minutes show that 93% of N95 respirators passed the fit test if the respirator was donned and doffed less than 5 times prior to dry heat decontamination ( Zha et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional work studying the electrostatic charge on mask filter layers, which is partially responsible for filtering of small particles by electrostatic adsorption, found that dry heat treatment at low humidities (< 30% RH) and low temperatures (< 100 °C) for 20 cycles did not decay the electrostatic charges and the efficiency of the filters ( Campos et al, 2020 , Liao et al, 2020 ). Fit tests conducted by Zha et al after one cycle of dry heat decontamination at 75 °C for 30 minutes show that 93% of N95 respirators passed the fit test if the respirator was donned and doffed less than 5 times prior to dry heat decontamination ( Zha et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…We chose 25 °C to correspond to standard ambient conditions. We chose 70 °C as our maximum temperature for three reasons: (i) it is the lowest setting in typical home ovens; (ii) it has been suggested as a dry heat decontamination temperature by the FDA; and (iii) 70 °C is a typical temperature used for pasteurization ( Iijima et al, 2001 , Islam and Johnston, 2006 , Xiang et al, 2020 , Zha et al, 2021 ). Surgical masks (Canuxi Disposable Face Masks, SKU 810484847) were cut into 5 cm by 5 cm samples and inoculated with SARS-CoV-2 virus stock.…”
Section: Methodsmentioning
confidence: 99%
“…The degradation of the components of N95/PFF2 masks can be exacerbated by the intense routine of health professionals, who often need to don and doff several times during the workday, especially for essential breaks such as hydration, eating, and even face rest ( 9 , 15 ) . Researches carried out in health services show a variation in the frequency of donning, ranging from up to five occurrences in ten-hour shifts and an average of forty in twelve-hour shifts ( 26 - 27 ) . Therefore, it is vital that users carry out rigorous visual inspections and check the seal of N95/PFF2 masks before each use to ensure the integrity of these devices is maintained and, consequently, ensure effective protection against airborne infectious agents ( 4 - 5 , 28 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Efforts were quickly mobilized to ensure a PPE re‐sterilization process was in place as with many medical institutions worldwide 14 . Development of alternative PPE options were quickly developed to ensure a steady supply of masks, gowns, and gloves While N‐95 masks were decontaminated and re‐worn for a longer duration, there was no indication that this significantly lessened their efficacy in protecting against COVID‐19, if used in short intervals, though their reuse was suboptimal 32–34 . However, despite actual access to PPE, employees still reported stress related to feelings of inadequate PPE.…”
Section: Discussionmentioning
confidence: 99%
“…14 Development of alternative PPE options were quickly developed to ensure a steady supply of masks, gowns, and gloves While N-95 masks were decontaminated and re-worn for a longer duration, there was no indication that this significantly lessened their efficacy in protecting against COVID-19, if used in short intervals, though their reuse was suboptimal. [32][33][34] However, despite actual access to PPE, employees still reported stress related to feelings of inadequate PPE. These findings are consistent with a report indicating health care worker disapproval of N-95 reuse practices, 35 which is a plausible cause of PPE-related stress.…”
Section: Discussionmentioning
confidence: 99%